High-intensity focused ultrasound for prostate cancer. (3rd May 2020) - Napoli, Alessandro; Alfieri, Giulia; Scipione, Roberto; Leonardi, Andrea; Fierro, Davide; Panebianco, Valeria; De Nunzio, Cosimo; Leonardo, Costantino; Catalano, Carlo
ABSTRACT: High-intensity focused ultrasound (HIFU) is a noninvasive procedure that has shown promising results in a wide range of malignant and nonmalignant conditions, including localized prostate cancer (PCa). This review aims to describe the application of HIFU in the management of patients with PCa, explaining its basic therapeutic principles, going through the main phases during aHIFU session, and providing an overview of the main available pieces of evidence from literature. HIFU treatment for prostate cancer is increasingly performed with high success and safety. MR guidance (MR-guided HIFU) has the advantage of real-time intraprocedural thermometric feedback that ensures that the whole region of interest has been covered by critical thermal damage (and that all surrounding healthy tissues have been spared). The absence of comparative long-term trials prevents HIFU from being considered as afirst choice for the treatment of patients with PCa.